Book review: Mischa Hansel, Raphaëlle Khan, and Mélissa Levaillant (Eds), Theorizing Indian Foreign Policy. (September 2019) - Chandra, Vikash
Mischa Hansel, Raphaëlle Khan, and Mélissa Levaillant (Eds), Theorizing Indian Foreign Policy . New York: Routledge, 2017, pp. x + 225, £29.99 (Paperback). ISBN 978147246238 (hardback), ISBN 9781315551197 (e-book).